2015
DOI: 10.1152/japplphysiol.00317.2015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training causes differential changes in gene expression in diaphragm arteries and 2A arterioles of obese rats

Abstract: We employed next-generation, transcriptome-wide RNA sequencing (RNA-Seq) technology to assess the effects of two different exercise training protocols on transcriptional profiles in diaphragm second-order arterioles (D2a) and in the diaphragm feed artery (DFA) from Otsuka Long Evans Tokushima Fatty (OLETF) rats. Arterioles were isolated from the diaphragm of OLETF rats that underwent an endurance exercise training program (EX; n = 13), interval sprint training program (SPRINT; n = 14), or remained sedentary (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…A recent series of studies evaluated the effects of regular exercise on the vascular transcriptome in pigs (238) and rats (174,175,235). A common finding is that the effects of exercise are heterogeneous across vascular beds.…”
Section: Changes In Vascular Cell Gene Expression Induced By Exercmentioning
confidence: 99%
“…A recent series of studies evaluated the effects of regular exercise on the vascular transcriptome in pigs (238) and rats (174,175,235). A common finding is that the effects of exercise are heterogeneous across vascular beds.…”
Section: Changes In Vascular Cell Gene Expression Induced By Exercmentioning
confidence: 99%
“…[15][16][17]27 Nevertheless, the notion that the effects of exercise are not the same among skeletal muscle arteries can be reconciled with the understanding that during exercise different muscle fiber recruitment patterns exist among these skeletal muscles, thus likely contributing to this differing vascular effect of training between muscles and even within muscles. 17,27 Perhaps more surprising was our recent finding that obesity, viewed as a condition with systemic complications, also resulted in striking heterogeneous effects among arteries examined. 24,28,29 Indeed, we identified 20 genes whose expression was consistently altered among 15 arteries, which represented only a $9% overlapping effect of obesity among all arteries examined.…”
Section: Discussionmentioning
confidence: 99%
“…The EXT components of the study indicated that both types of EXT caused heterogeneous patterns of altered gene expression within and among the arteriolar trees of these three muscles in T2D (OLETF) rats . For example, SIT training altered expression of 445 genes with differential expression in the diaphragm FA, 171 genes in the SFA, and 16 genes in the gastrocnemius FA, yet there were only two genes that had increased expression in all three FAs .…”
Section: Ext‐induced Adaptations Of Vascular Structure and Function Amentioning
confidence: 95%
“…We used the OLETF rat model to examine the interactive effects of EXT and obesity/T2D on the skeletal muscle arteriolar tree. Importantly, we used arteriolar samples taken from the same animals used for the studies of vasomotor reactivity to determine transcriptional profiles with techniques described previously . The EXT rats had lower body weights and higher heart weight/body weight ratios, lower percent body fat and % HbA1c, and increased citrate synthase activity of the red and white portions of the vastus lateralis muscle.…”
Section: Ext‐induced Adaptations Of Vascular Structure and Function Amentioning
confidence: 99%